COVID-19 Infodemic: Underlining the importance of digital literacy skills - Sari, Komang Ayu Kartika (Public Health and Preventive Medicine Archive, 2021)
The massive spread of online information, high access to internet and social media, and inadequate digital literacy among Indonesian have been a combination to accelerate the spread of infodemic that indicates the need for a better approach in countering COVID-19 infodemic. Collaboration between the community, social media platforms and the government is required to improve Indonesian digital literacy. The government, both at the national and sub-national levels, need to start a digital literacy campaign by actively involve the community to educate and empower them in searching, checking and spreading various information available in digital platforms. Community involvement should be started from family level as first gatekeeper to prevent spread of incorrect information as well to filter the correct one before circulating it inside and outside their family circle. Family members can be reached through local community organisations or programs such as Karang Taruna and Pemberdayaan Kesejahteraan Keluarga (PKK). Schools also need to get involved by including digital literacy in the current national curriculum starting from the early years of primary school. Social media platforms and official websites of both governmental and nongovernmental organisations have currently responded to COVID-19 infodemic by taking several actions such as flagging, filtering, blocking and removal content or accounts, etc, which are identified or reported suspicious. Nevertheless, those efforts must be supported by the government regulation to combat disinformation, particularly for the digital media companies in Indonesia. Strong and sustainable collaboration between the community, social media platforms and the government is important to achieve the good level of Indonesian digital literacy skills and to tackle the COVID-19 infodemic.